MANTRA AND YANTRA IN TANTRA - A K Chappanath (Journal of Dharma, 1977)
Tantra is generally regarded as a system of black magic. It is the most neglected branch of Indian thought. Though tantra has 31 rich spiritual heritage and a sublime philosophy, the siidbana of paiicbamaledra (five M’s)has given a good deal of misunder- standing about the tantric spirituality. Tantra is full of symbolism and its mantras and yantras will simply appear as nonsensical syllables and diagrams to a layman. But for the initiated mantra and yantra become sources of mystic power capable of liberating one from the bondage of this world.